تقييم كفاءة المصائد وبعض إجراءات الإدارة الآمنة في السيطرة على القوارض ضمن بيئة الحمضيات في منطقة جبلة - صقر, إبراهيم; شاهين, هيثم; جبور, ردينة (Latakia University Journal -Biological Sciences Series, 2019)
بهدف السيطرة على القوارض في البيئة الزراعية المأهولة، والتخفيف من أضرارها، نفذت هذه الدراسة ضمن بيئة الحمضيات في جبلة باستخدام مجموعة إجراءات آمنة ( بيئية، زراعية وكيميائية) تتبع إدارة الآفة وإدارة المخلفات. ثبت تراجع أعداد القوارض كثيراً في معاملة إدارة الآفة(70.37 %) وبنسبة لا بأس بها لدى معاملة إدارة المخلفات (55.56 %) مقارنةً مع الشاهد. سجل التراجع الأكبر في أعداد القوارض لدى نوعي المصائد الموزعة, وفي أعداد الثمار المتضررة بالقوارض عموماً عند التكامل بين إجراءات الإدارتين. وقد زادت كفاءة الأساليب المتبعة في السيطرة على القوارض, وبالتالي حماية محصول الحمضيات مع تكامل إجراءات الإدارتين من جهة, ومع توالي تطبيقها لسنوات عديدة من جهة ثانية، حيث وصل التراجع في أعداد القوارض و أعداد الثمار المتضررة نهاية العام 2009 إلى 85.19 و 100 % على التوالي مقارنة مع الشاهد. تؤكد نتائج البحث أهمية وإمكانية الاعتماد على بعض الإجراءات الآمنة للتخفيف من استخدام المبيدات لمكافحة القوارض ولتحقيق سيطرة مقبولة عليها في الأماكن الزراعية المأهولة. In order to control rodents in the inhabited agricultural environment and to reduce their damage, this study has been conducted in the citrus environment in Jableh with safe procedures (environmental, agricultural and chemical ) which follow pests and residues management. A large decline in the number of rodents has been proved with the pests management treatment (70.37 %) and with acceptable number in residues management(55.56 %) compared with the witness . The biggest decline in rodent numbers has been recorded with two basic kinds of the distributed traps and in the number of the infected fruit by rodents with the integration between the procedures of the two managements . The capacity of the applied ways increased the control of rodents and consequently the protection of the citrus crops with the integration between the two managements, on one hand, and with the repeated use for many years, on the other hand . The decline rate in the number of the rodents and in the number of the damaged fruit at the end in 2009 reached 85.19 and 100 % in comparison with the witness . The research result proves the importance and the possibility of depending on some safe procedures to reduce the use of pesticide in controlling rodents and to achieve an acceptable control of rodents in the inhabited agricultural areas.